2016
DOI: 10.12659/msm.900349
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Phosphoprotein 3 Inhibits the Apoptosis of Human Glioma Cells in Part by Downregulating N-myc Downstream Regulated Gene 1

Abstract: BackgroundGolgi phosphoprotein 3 (GOLPH3) has been reported to be involved in the development of several human cancers. Our previous study showed that GOLPH3 expression in glioma tissues was related to the severity of the malignancy of the cancer. However, the mechanism by which GOLPH3 affects cell apoptosis is largely unknown. The present study was designed to explore the possible mechanism of GOLPH3 in cell apoptosis.Material/MethodsTo analyze the biological role of GOLPH3 in glioma cells, we used GOLPH3 sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As such, NDRG1 is considered a bona fide tumor suppressor. In a recent work [72], the authors showed that GOLPH3 knockdown in U251 promotes glioma cell apoptosis and increases cellular levels of both NDRG1 and cleaved caspase 3 by 55% and 80%, respectively. On the other hand, NDRG1 knockdown does not affect GOLPH3 expression but lowers the level of cleaved caspase 3, suggesting that GOLPH3 increases the cleavage of caspase 3 and apoptosis of glioma cells partially via downregulating NDRG1.…”
Section: Golph3 Deregulation and Brain Tumorsmentioning
confidence: 99%
“…As such, NDRG1 is considered a bona fide tumor suppressor. In a recent work [72], the authors showed that GOLPH3 knockdown in U251 promotes glioma cell apoptosis and increases cellular levels of both NDRG1 and cleaved caspase 3 by 55% and 80%, respectively. On the other hand, NDRG1 knockdown does not affect GOLPH3 expression but lowers the level of cleaved caspase 3, suggesting that GOLPH3 increases the cleavage of caspase 3 and apoptosis of glioma cells partially via downregulating NDRG1.…”
Section: Golph3 Deregulation and Brain Tumorsmentioning
confidence: 99%
“…Depletion of GOLPH3 or MYO18A increases cancer cells' sensitivity to DNA damage inducing agents, suggesting that GOLPH3 phosphorylation-induced Golgi fragmentation may serve as a protective mechanism (Farber-Katz et al 2014). Considering that GOLPH3 is overexpressed in many solid tumors, it is reasonable to speculate that this may be a mechanism of how cancer cells escape DNA damage-induced apoptosis (Farber-Katz et al 2014;Buschman et al 2015;Li et al 2016b).…”
Section: Golph3 and Dna Damage-induced Golgi Fragmentationmentioning
confidence: 99%
“…Following a general streptavidin-biotin complex immunohistochemical protocol (9), immunoreactivity was visualized with diaminobenzidine and the nuclei were counterstained with hematoxylin. Sections were then subsequently dehydrated in a series of graded alcohols, cleared in xylene and mounted.…”
Section: M M U N O H I S T O C H E M I C a L S T A I N I N G P R O mentioning
confidence: 99%